Police officers' discourses about male victims of intimate partner violence in Portugal. (December 2021) - Machado, Andreia; Campos, Maria; Matos, Marlene
Abstract: Intimate partner violence is a well-known social, criminal and health problem. The victim's characteristics have been changing in the last years, however, intimate partner violence against male victims has not yet been the subject of sufficient social or scientific attention. The police, for many victims, is the first contact when calling for help. The present study analyses the discourses of police officers on male victims of intimate partner violence and explore their experiences and difficulties when men are the victims. In depth interviews with police officers ( n  = 11) were conducted and data was analyzed according to content analysis which allowed the identification of three major themes: IPV in general, IPV against males and the role of the police officers. The findings showed that police officers have an adjusted knowledge on the phenomenon (e.g., prevalence; types of violence; characterization of IPV; reasons for female aggression; role of police). Yet there seems to be some grey areas when it comes to more specific questions (e.g., characteristics of the perpetrators; impact on the victim; coping strategies to deal with violence), which can contribute to difficulties for male victims to report intimate partner violence and receive a helpful service. The practical implications of these qualitative findings for police, male victims and the scientific community are discussed.